Imobilização da enzima frutosiltransferase extracelular de Aspergillus oryzae IPT-301 em sabugo de milho para a produção de fruto-oligossacarídeos - Pereira, Richard Silveira (2021)
Fructooligosaccharides (FOS) are beneficial foods to the human organism. Commercially, they are synthesized through a transfructosylation reaction, in which a transferase enzyme catalyses sucrose in FOS. Among the microorganisms that produce these enzymes, the Aspergillus oryzae IPT-301 stands out for producing fructosyltransferase (FTase) with high transfructosylation activity (A_t). The use of free enzymes on a commercial scale is a difficult and costly process, as it is easily denatured. Therefore, there is a need to research the immobilization of these enzymes intending to increase their half life time and their stability. Thereby, this work aimed to evaluate the immobilization process of the extracellular FTase (by physical adsorption) in corn cob, a natural agro-industrial waste. The support in natura was just grated. The corn cob was functionalized by alkali extraction to maximize its adsorption capacity. It was made assays to evaluate the kinetics of the FTase immobilized in corn cob for several temperatures. It was made a design of experiments intending to study the influences of temperature and pH over the A_t and their optimum conditions. It was evaluated the thermal, operational, substrate concentration, and pH stabilities. The kinetic models of immobilization pointed that the A_t of the fermented broth (in contact with the support) decreased along with the assay, wherein the best immobilization yield (RI) was for 35 °C (74 % for the support in natura and 64% for the functionalized one). The recovered transfructosylation activity (A_tr) resulted in a value around four times superior for the functionalized corn cob (9,05 ± 0,58 %), indicating the support functionalization increased its adsorption capacity. The design of experiments showed that the optimum conditions for the heterogeneous biocatalyst were 55 °C and pH 5.5. The assays for the concentration effects showed that the highest activities were reached for concentrations between 400 g.L-1 and 600 g.L-1, and the enzymatic kinetic was best adjusted to the Hill model. The assays for the pH stability indicated that the heterogeneous biocatalyst was stable for the pH range between 5.5 and 6.0. The subsequent assay indicated that there was not an expressive increase of the thermal stability of the heterogeneous biocatalyst in face soluble one, with half life time (of the heterogeneous biocatalyst) 1.13 time superior for 50 °C. The operational stability assay allowed to verify that the FTase immobilized in functionalized corn cob kept it relative A_t up to 13 % at the end of the fourth batch cycle, pointing to its reuse possibility. Thus, it was concluded that the characterization and stability assays allowed it to observe that the FTase was immobilized in corn cob by physical adsorption. It is called attention to the fact that this research is innovative in immobilizing fructosyltransferase in waste for the production of fructooligosaccharides.